Knowledge About Immunosuppressant Medication and Its Correlates in a German Kidney Transplant Population – Results of a KTx360° Substudy - de Boer, Sophie (Patient Prefer Adherence, 2020)
PURPOSE: After organ transplantation, adherence to immunosuppressive medication (ISM) is crucial to prevent organ rejection. To enable adherence, patients need to be well informed about the different aspects associated with their ISM. However, literature suggests that knowledge regarding ISM is often inadequate. PATIENTS AND METHODS: In a cross-sectional study, 702 patients after kidney transplantation participating in a structured multimodal follow-up program (KTx360°) were evaluated. We utilized a self-developed questionnaire which has been successfully used before to measure patients’ knowledge about the ISM. Above that we aimed to evaluate potential associations between sociodemographic, medical, donation-specific, and psychosocial variables including adherence, levels of depression and anxiety, perceived social support, and cognitive functioning with the knowledge level. RESULTS: The mean age of the patients was 52.4 years, 58.1% were men, and 66.6% were living in a partnership. The mean time since transplantation was 65.1 months. On average, patients answered 70.9% of the questions correctly. The percentage of correct answers per question differed considerably (54%–92%). In univariate analyses, knowledge levels were positively associated with female gender, current partnership, German as first language and better cognitive functioning. However, the effect sizes were small. CONCLUSION: Taking into account that the patients after KTx can be expected to answer all questions correctly as they aim at basic knowledge, an average result of 70.9% corresponds to a moderate knowledge level. Consequently, the current educational approaches do not seem to be sufficient to inform all patients adequately. Further research is necessary on how to improve health knowledge in the long term.